POTENSI LIMBAH PADAT KELAPA SAWIT: PELEPAH KELAPA SAWIT DAN TANDAN KOSONG KELAPA SAWIT SEBAGAI BAHAN BAKU BIOETANOL - Akladius L. Sani Simanjuntak; Ika Ucha P. Rangkuti; M. Hendra Ginting (Institut Teknologi Sawit Indonesia (ITSI), 2021)
The global oil energy crisis is caused by the imbalance between consumption and production of petroleum. Inorder to compensate for this imbalance, the conversion of organic waste and biomass into fuel is carried outappropriately and quickly. This review article aims to determine the potential for solid waste from oil palm,Oil Palm Empty Bunches (TKKS) and Palm Oil Palm Ribs (PKS) as raw materials for making bioethanol. Theproduction process of ethanol from palm oil solid waste is carried out starting from lignocellulosicpretreatment using alkaline and oxidation methods, with the highest results getting a decrease in lignincontent in the EFB substrate from 35.51% to 9.47% or a decrease of 73.33%, while cellulose andhemicellulose content increased by 69% and 20.68% respectively, then the hydrolysis process with acid andenzyme catalysts with the highest yield obtained glucose levels of 60.02%, followed by a fermentation processusing Saccharomyces Cerevisiae with the highest yield of ethanol content of 7.93%. Utilization of empty oilpalm fruit bunches (TKKS) and oil palm midribs (PKS) as raw materials for the manufacture of bioethanolhas enormous potential.